Penerapan Salat Dhuha dalam Pembentukan Karakter Siswa Kelas V Madrasah Ibtidaiyah Negeri 1 Malang: Tinjauan Karakter Moral Thomas Lickona - Fitratul Uyun (Fakultas Agama Islam Universitas Billfath, 2023)
Moral character is everything related to evaluating good and bad actions. The importance of internalizing moral concepts in children from an early age is because this period is a crucial period or phase for building moral intelligence. This process not only involves habits, but also involves awareness, understanding and practice of good moral values. The aim of this research is to examine how the implementation of the first prayer and the prayer after it plays a role in raising the enthusiasm of students at MIN 1 Malang City, especially for Class V MIN 1 Kota Malangst udents. Using qualitative methods, data was collected through observation, interviews and recording. Data analysis includes reduction, presentation and drawing conclusions. The results of the research show that: (1) The implementation of the dluha prayer carried out by MIN 1 Kota Malang students has formed an initial moral understanding that is consistent with the indicators of daily practice of the dluha prayer practice carried out from grades one to six. Students have reached the stage of moral awareness, understanding moral values, and forming perspectives; (2) After studying the material on the first prayer, class V MIN 1 Kota Malang students also received an introduction to prayer in the second semester of Fiqh subjects. Thus, students' moral emotions have developed, including awareness of conscience, sense of self-worth, and empathy; (3) The implementation of the Dluha prayer has contributed to shaping students' morality, where they have now reached the stage of ability, desire and habits in implementing these moral values as stated by Lickona. The habit of performing the Dluha prayer greatly contributes to the formation of students' moral character, so it is highly recommended to be part of students' education and learning at school.